Selective Synthesis of Fe2O3 and Fe3O4 Nanowires Via a Single Precursor: A General Method for Metal Oxide Nanowires - Du Ning; Xu Yanfang; Zhang Hui; Zhai Chuanxin; Yang Deren (Nanoscale Research Letters, 2010)
Abstract Hematite (α-Fe2O3) and magnetite (Fe3O4) nanowires with the diameter of about 100 nm and the length of tens of micrometers have been selectively synthesized by a microemulsion-based method in combination of the calcinations under different atmosphere. The effects of the precursors, annealing temperature, and atmosphere on the morphology and the structure of the products have been investigated. Moreover, Co3O4 nanowires have been fabricated to confirm the versatility of the method for metal oxide nanowires.